2013
DOI: 10.1159/000343362
|View full text |Cite
|
Sign up to set email alerts
|

miR-30a Suppresses Cell Migration and Invasion Through Downregulation of PIK3CD in Colorectal Carcinoma

Abstract: Background/Aims: MicroRNAs (miRNAs) play key roles in tumor metastasis. The aim of this study was to determine the regulation and function of miR-30a in colorectal carcinoma (CRC) metastasis. Methods: The expression of miR-30a was detected in CRC cell lines and samples by qRT-PCR. The anti-metastatic effect of miR-30a was determined by both in vitro and in vivo assays. A luciferase reporter assay was performed to determine target association between miR-30a and phosphoinositide 3-kinase catalytic subunit delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 31 publications
2
72
0
Order By: Relevance
“…Several studies demonstrated that miR-30a could reduce the oncogenic abilities of breast cancer and lung cancer by inhibiting epithelial-to-mesenchymal transition (EMT), invasiveness, and autophagy of cancer, depending on their targets (10,11,21). In particular, two other studies have shown that miR-30a is able to induce growth inhibition and cell migration and invasion suppression in colorectal cancer by targeting DTL and PIK3CD, respectively (22,23). In line with these observations, we found that miR-30a acts as a tumor suppressor by targeting IRS2.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that miR-30a could reduce the oncogenic abilities of breast cancer and lung cancer by inhibiting epithelial-to-mesenchymal transition (EMT), invasiveness, and autophagy of cancer, depending on their targets (10,11,21). In particular, two other studies have shown that miR-30a is able to induce growth inhibition and cell migration and invasion suppression in colorectal cancer by targeting DTL and PIK3CD, respectively (22,23). In line with these observations, we found that miR-30a acts as a tumor suppressor by targeting IRS2.…”
Section: Discussionmentioning
confidence: 99%
“…miR30 family members are among one of the most dysregulated miRNAs in metastatic cancers, each with a potential role in cancer metastasis (21). Although miR30a expression has been reported to be downregulated in metastatic breast cancer and colorectal cancer, its tumor suppressor function is not well understood (22,23). Specifically, downregulation of miR30a in ATC has been previously reported but overexpression of this miRNA did not affect cell proliferation in two ATC cell lines (FRO, FB-1; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that the miR-30 family plays important roles in pronephros development, hepatobiliary duct formation, and myogenesis in zebrafish (Agrawal et al, 2009;Hand et al, 2009); the miR-30 family also regulates cancer metastasis in humans and mice (Zhong et al, 2013;Zhang et al, 2016). However, the roles of the miR-30 family in neuroimmunological diseases have not been reported.…”
Section: Discussionmentioning
confidence: 99%